Exercise haemodynamics of coarctation of the aorta: Acute effects of propranold - Cumming, Gordon R. (1970)
Eight patients with aortic coarctation were studied at rest and during supine bicycle exercise before and after intravenous propranolol 0·17 mg./kg. The mean pressure gradient across the aortic narrowing increased from 16 to 45 mm. Hg during exercise, and was reduced to 11 and 31 mm. Hg after propranolol. Total peripheral resistance was increased by propranolol both at rest and during exercise, and the diminished pressor response was due to a 20 per cent decrease in exercise cardiac output. Brachial artery systolic pressure was reduced more than central aortic systolic pressure in 2 of the 3 patients in whom both pressures were monitored. In one patient descending aortic pressure fell during exercise; in the remainder, slight increases were noted.